Detection of Antibioties Residue in Broiler Carcass - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT Antibiotics have long been used in poultry industry and its wide application was beciiiise the medicine are readily .available at the markets. The research of antibiotics residues detection in broiler carcass was conducted from February I to March 31, 1994. Fitly samples of broiler's breast and tissues from 5 local markets (Bogor, Kebon Iclembang. ltamayana.Gembrong and Cumpok) were used in this experiment Residue of antibiotics was detennincd using microlnological method. In this test Bacillus SicarothernwphiluN. Strain Doak (Ncre 10339, ATTC 12980. NC.113 8923, BCC 611) was used From 50 samples of breast and thighs tissues being studied, it was found that 12 samples of breast tissue (24%) and 7 samples of thigh tendon (14%) contained an antibiotic. The results of an interview with the broiler breeders and medicine sellers indicated that most widely used type of antibiotic Waq itniphyoltn